Legal Aspect of a Will Made Before a Notary by Divorced Parents - Suartining, Ni Ketut; Perbawa, Ketut Sukawati Lanang P. (Journal of Social Research, 2023)
This study aims to determine the legal aspects of a will made before a notary by divorced parents, with the formulation of the problem: What are the legal aspects of a will whose object is joint property made after the parent’s divorce?; What is the legal protection for beneficiaries of wills made by divorced parents? This study uses a normative legal research method, using a literature study approach, also equipped with an analysis of laws and regulations related to bequests of joint property objects, as well as reviewing some of the literature, research results related to the topic of writing, opinions of competent experts and several scientific journals. Furthermore, the collected data was processed and analyzed qualitatively and then described descriptively. As for the research hypothesis, everyone who is going to make a will must first know and study the limits of his assets that he can bequeath to other people and must first issue the rights of heirs before bequeathing his inheritance to other parties. Regulations regarding the rights of the longest living partner have been explicitly and in detail contained in the BW, such as regarding Legitime Portie rights. Legal protection for the recipient of the will, when examined from article 1365 BW, the recipient of the will actually can experience material and immaterial losses. Material losses can be in the form of a joint price because the Notary is without the knowledge of the Treasure Hall and the reading and submission to the wrong party.